Photothermal imaging using photopyroelectric and dual-beam mode-mismatched thermal lens method for defect study on transparent materials - Ting, Lee Mon (2019)
This research is carried out mainly to study the defect by comparing thermal images obtained from PPE setup and dual-beam mode-mismatched thermal lens method setup. The laser beam is optimized first to select the most suitable laser beam for thermal imaging process for PPE setup and dual-beam mode-mismatched thermal lens method setup. Blue laser is chosen as the main laser source for thermal imaging process. Thermal imaging process is performed using PPE setup and dual-beam modemismatched thermal lens method setup to obtain the thermal images for samples of no defect, crack defect, line defect and hole defect. Comparison between thermal images obtained from PPE setup, two mirrors dual-beam mode-mismatched thermal lens setup and one mirror dual-beam mode-mismatched thermal lens setup are performed. Thermal images from PPE show the most stable results, two mirrors dual-beam mode-mismatched thermal lens setup show slightly fluctuate thermal images but with better view for defect studying, whereas one mirror dual-beam mode-mismatched thermal lens setup show the most fluctuation thermal images with an easier in data collecting when compare to two mirror dual-beam mode-mismatched thermal lens setup.